Temperature compensation in ball screws of CNC machines - Тарас Скрипник; Володимир Кореньков (Mechanics and Advanced Technologies, 2025)
Thermal deformation of ball screw feed drives is a major source of positioning error in high-speed CNC machine tools. Frictional heat generated during rapid screw motion causes expansion and leads to significant deviations at the tool center point. This literature review compiles recent advances in temperature compensation techniques for ball screws, focusing on approaches to model and compensate thermal errors, methods for measuring temperature on moving feed axes, and techniques for evaluating positioning accuracy. A wide range of compensation methods are examined, from physics-based thermal models and empirical regression models to modern machine learning and hybrid approaches. Various sensor strategies for capturing temperature—contact thermistors, wireless embedded sensors, and infrared thermography—are compared in terms of responsiveness and practicality. Methods for quantifying thermal elongation and positioning error, such as laser interferometry and other high-precision measurement systems, are also reviewed. The review finds that data-driven (empirical) modeling techniques, non-contact temperature sensing, and laser-based accuracy measurements have shown particular promise.